PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN DAN KUALITAS AUDIT TERHADAP TAX AVOIDANCE (STUDI EMPIRIS PADA PERUSAHAAN SUB INDUSTRI NIKEL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021 – 2024) - Risma Udur Br. Sitorus Pane; Dicky Arisudhana (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
Tax avoidance is an action aimed at reducing taxable income through tax planning, either by complying with applicable regulations or otherwise. This study aims to examine the effect of profitability, leverage, firm size, and audit quality on tax avoidance, which is measured using the Effective Tax Rate (ETR) proxy, in nickel sub-sector mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This study uses secondary data with a population of 44 nickel sub-sector mining companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The sampling technique used is purposive sampling, and the data are analyzed using multiple linear regression analysis. The results of this study indicate that partially and simultaneously, profitability and firm size quality have a significant effect on tax avoidance. Meanwhile, leverage and audit does not have a significant effect on tax avoidance. The practical implication of this study is that it can be used as a consideration for companies in making business decisions, particularly in their taxation activities.